[Ulotka. Incipit:] Wniosek o nadanie odznaki honorowej "Zasłużonym Ziemi Gdańskiej". (Gdańsk : [wydawca nieznany], 1967)
Formularz wniosku.
Keywords: 1901-2000; 1945-1989; Gdańsk (woj. pomorskie); Druki ulotne